Synergetic effects of Bi⁵⁺ and oxygen vacancies in Bismuth(V)-rich Bi₄O₇ nanosheets for enhanced near-infrared light driven photocatalysis - Liu, Jin (2022)
The appropriate energy level position of photocatalysts dominates the photocatalytic redox reaction and utilization efficiency of solar energy for wastewater treatment. Herein, we report a near-infrared (NIR) light driven Bi5+-rich Bi4O7 photocatalyst, achieving a greatly enhanced photocatalytic activity for pollutant removal compared with Bi3+-replenished Bi2O3. Density functional theory calculations show the formation of an intermediate band in the Bi4O7 structure because of the hybridization of O 2p and Bi 4s orbits. The formation of the intermediate band not only narrows the band gap but also improves the optical absorption property and separation efficiency of the photoinduced carriers. The existence of the oxygen vacancies (OVs) in the Bi4O7 nanosheets ensures high carriers’ concentration, which is verified by the Hall effect test. The synergetic effects of the OVs and Bi5+ greatly accelerate the separation efficiency of the photogenerated carriers. Consequently, the Bi4O7 nanosheets exhibit enhanced NIR light driven photocatalytic activity for the degradation of rhodamine B and ciprofloxacin compared with the bulk Bi2O3. This study paves the way to the design of highly efficient NIR light-responsive Bi-based photocatalysts for environmental purification.